Peran Guru Pendidikan Agama Islam (PAI) Dalam Meningkatkan Kedisiplinan Siswa Di Pondok Pesantren Tahfidz Al-Mubarok Pajo - Mukhlisin (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2023)
This research method uses qualitative writing methods. Data collection techniques used in this study, using interviews, observation, and documentation. While the data analysis in this study used a qualitative descriptive technique. The role of PAI teachers in improving student discipline, (1) As supervisors, Islamic religious education teachers always provide direction and advice to students to always be disciplined and obey the rules, both at school and outside of school. (2) As a motivator, they always encourage their students to be enthusiastic and active in learning and to always be disciplined in obeying the rules that apply at school, the form of encouragement they give is by saying that many of their seniors are successful because they are always disciplined in learning. (3) as an example is a teacher who always teaches students to always be disciplined, PAI teachers come on time, maintain tidiness, train students to dispose of trash in its place.